Bio-based Materials for Food Packaging Green and Sustainable Advanced Packaging Materials (Springer Singapore, 2018)
This book provides an overview of the lastest developments in biobased materials and their applications in food packaging. Written by experts in their respective research domain, its thirteen chapters discuss in detail fundamental knowledge on bio based materials. It is intended as a reference book for researchers, students, research scholars, academicians and scientists seeking biobased materials for food packaging applications.